Analysis of Cognitive Skills in History Textbook (Spain-England-Portugal) - Cosme J. Gómez; Glória Solé; Pedro Miralles; Raquel Sánchez (Frontiers in Psychology, 2020)
The main objective of this article is to analyze the cognitive level of the activities in History textbooks in Spain, England, and Portugal in the transition stage from Primary to Secondary Education (11–13 years), according to the country of origin, typology, and the concepts and disciplinary contents included. The design of this research is quantitative, descriptive, and cross-sectional. The non-probabilistic sample consists of 6,561 activities contained in 27 school textbooks from Spain, England, and Portugal. Descriptive and contrast analyses have been carried out using parametric tests. The results indicate that textbooks from Spain and Portugal mainly include activities situated between a basic and intermediate cognitive level while in England, the cognitive level of activities is medium or high. The ANOVA and Tukey B tests show significant differences between the cognitive level required in the activities and the typology of exercises, the concepts, and historical contents worked on. The activities with higher cognitive level correspond to those of creation and essays, the exercises that work on empathy and historical relevance, and that contain activities of social and economic history. In contrast, the activities with the lowest cognitive level are short questions and objective tests, those that work on first-order concepts (data and concrete facts), and those on the History of Art. The conclusion is that there is a need for a balanced presence of first-order content and historical thinking skills, the application in the classroom of a more active student-centered methodology, and the teachers’ conception of history teaching that prioritizes historical skills.